Characterization of Marine Mammal Recordings from the Hawaii Range Complex - Baumann-Pickering, Simone; Baldwin, Lisa K.; Simonis, Anne E.; Roche, Marie A.; Melcon, Mariana L.; Hildebrand, John A.; Oleson, Erin M.; Baird, Robin W.; Schorr, Gregory S.; Webster, Daniel L.; McSweeney, Daniel J. (Monterey, California. Naval Postgraduate School, 2010)
This report summarizes work conducted in FY2009-FY2010 to characterize marine mammal sounds related to passive acoustic monitoring in the Hawaii Range Complex. Existing acoustic data from the Complex were analyzed to provide better descriptions of acoustic signals by species. Recordings were from a boat-based hydrophone or an autonomous bottom-moored High-frequency Acoustic Recording Package (HARP). Recordings were made of pygmy killer whales, melon-headed whales, Risso's dolphins, and rough-toothed dolphins. Echolocation click parameters were calculated for single species recordings during visual and acoustic surveys by boat-based hydrophones, and by using sightings from small boat surveys and locations of satellite tagged individuals near the HARP. Automatic classification of echolocation clicks of false killer whales and short-finned pilot whales was performed using a Gaussian mixture model. An analyst manually screened the HARP data collected off the west coast of Hawaii during the period ii/10/2009-iii/9/2009. Distinct call types were found for: beaked whales with frequency modulated upsweep echolocation pulses; sperm whales; high frequency clicks of unknown origin; low frequency banded echolocation clicks; and a large number of unidentified echolocation clicks. Odontocetes were acoustically active every day. Beaked whales were detected on 41% of recording days, but only briefly each day. N00244-08-1-0028 CNO(N45)